1997
DOI: 10.1002/hep.510250516
|View full text |Cite
|
Sign up to set email alerts
|

Urinary transforming growth factor ?1 levels in hepatitis C virus-related chronic liver disease: Correlation between high levels and severity of disease

Abstract: between cirrhotic nodules and fibrous septa, where active and PIIINP levels in patients (r Å .858, P õ .0001). The fibrogenesis occurs, is in accordance with the function of TGFhigher the urinary TGF-b 1 level, the worse the severity b 1 as a potent stimulator of the extracellular matrix. 22,24,25 In of chronic liver disease (P õ .001). TGF-b 1 levels in ciraddition, increased liver expression of TGF-b 1 mRNA correrhotic patients with antibodies to hepatitis C virus (antilates with various indicators of liver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 45 publications
(21 reference statements)
1
25
0
Order By: Relevance
“…The plasma TGFb1 levels after treatment resulting in clinical improvement, although decreased, however did not correlate with a-fetoprotein [129]. It has even been suggested that in patients with HCC and low production of a-fetoprotein, a finding of increased TGFb1 concentration in urine may be useful in the diagnosis [131]. In addition, the way of Smad3 phosphorylation, resulting in the creation of two possible isoforms, alters the final effect of TGFb1.…”
Section: Prace Poglądowementioning
confidence: 96%
“…The plasma TGFb1 levels after treatment resulting in clinical improvement, although decreased, however did not correlate with a-fetoprotein [129]. It has even been suggested that in patients with HCC and low production of a-fetoprotein, a finding of increased TGFb1 concentration in urine may be useful in the diagnosis [131]. In addition, the way of Smad3 phosphorylation, resulting in the creation of two possible isoforms, alters the final effect of TGFb1.…”
Section: Prace Poglądowementioning
confidence: 96%
“…15 A number of serological and urinary compounds such as procollagens, tissue inhibitors of metalloproteinases (TIMP), type IV S collagen, hyaluronic acid, and laminin and mediators of extracellular matrix production such as TGF-␤ have been evaluated as noninvasive markers of liver fibrosis. [16][17][18][19][20][21][22][23][24][25][26] Most of these studies have focused on using these markers in cross-sectional studies to diagnose the stage of liver fibrosis.…”
Section: H Epatitis C Virus (Hcv) Infection Is Character-mentioning
confidence: 99%
“…Nineteen studies evaluated use of serum AFP for detection of HCC. As shown in Table 1, 10 studies evaluated other serologic markers for HCC, 25,27-31,35,37-39 1 study evaluated urinary transforming growth factor ␤-1, 40 6 studies evaluated hepatic ultrasound (US), 26,[32][33][34][35]40 1 study evaluated computerized tomography (CT) and magnetic resonance imaging (MRI), 30 and 2 studies evaluated CT and US. 26,34 AFP.…”
Section: Resultsmentioning
confidence: 99%
“…Five of these 24 studies were in patients infected with hepatitis C alone, [25][26][27][28][29] and 19 were in patients with hepatitis B or C or both. 18,20,24,[30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] Ten of these studies were surveillance studies, 20,24,26,[30][31][32][33][34][35][36] and 14 were screening studies. 18,25,[27][28][29][37][38][39][40][41][42][43][44][45] No study was excluded solely for lack of appropriate histological or pathologic evidence of HCC.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation